Chromosome Aberration on Growth and Developmental Disorder - Eva Diah Setijowati; Herni Suprapti; Maria Widijanti Sugeng; Retno Dwi Wulandari (Fakultas Kedokteran Universitas Brawijaya, 2022)
Growth and development in humans begin at conception, which shows progress and interdependence. Normal children show the characteristic of growth and development. In children with growth and development disorder, chromosomal abnormality may be found. This study aimed to determine chromosomal abnormality in patients with growth and development disorder. The samples were taken from karyotype results of patients in the Medical Genetics Laboratory, Faculty of Medicine, Universitas Wijaya Kusuma Surabaya, from 2010-2020. The inclusion criteria were infants to adolescents aged 24 years and unmarried who experienced impaired growth and development, including sexual development. Chromosomal abnormalities were obtained from cytogenetic analysis using the G-banding method. From 75 samples with growth and development disorders, there were abnormalities in the number of autosomal chromosomes and sex chromosomes found in patients with Down syndrome, Turner syndrome, Klinefelter syndrome, and Edwards syndrome. Chromosomal structural abnormalities found were deletion, translocation, inversion, duplication, marker chromosome, and heteromorphism. This study showed the importance of karyotyping in children and adolescents with growth and developmental disorders.